Changes in Retinal Structure and Ultrastructure in the Aged Mice Correlate With Differences in the Expression of Selected Retinal miRNAs - Hermenean, Anca; Trotta, Maria Consiglia; Gharbia, Sami; Hermenean, Andrei Gelu; Peteu, Victor Eduard; Balta, Cornel; Cotoraci, Coralia; Gesualdo, Carlo; Rossi, Settimio; Gherghiceanu, Mihaela; D’Amico, Michele (Frontiers in Pharmacology, 2021)
Age and gender are two important factors that may influence the function and structure of the retina as well as susceptibility to retinal diseases. The aim of this study was to delineate the influence that biological sex and age exert on the retinal structural and ultrastructural changes in mice and to identify the age-related miRNA dysregulation profiles in the retina by gender. Experiments were undertaken on male and female Balb/c aged 24 months (approximately 75–85 years in humans) compared to the control (3 months). The retinas were analyzed by histology, transmission electron microscopy, and age-related miRNA expression profile analysis. Retinas of both sexes showed a steady decline in retinal thickness as follows: photoreceptor (PS) and outer layers (p < 0.01 for the aged male vs. control; p < 0.05 aged female vs. control); the inner retinal layers were significantly affected by the aging process in the males (p < 0.01) but not in the aged females. Electron microscopy revealed more abnormalities which involve retinal pigmented epithelium (RPE) and Bruch’s membrane, outer and inner layers, vascular changes, deposits of amorphous materials, and accumulation of lipids or lipofuscins. The age-related miRNAs, miR-27a-3p (p < 0.01), miR-27b-3p (p < 0.05) and miR-20a-5p (p < 0.05), were significantly up-regulated in aged male mice compared to controls, whereas miR-20b-5p was significantly down-regulated in aged male (p < 0.05) and female mice (p < 0.05) compared to the respective controls. The miR-27a-3p (5.00 fold; p < 0.01) and miR-27b (7.58 fold; p < 0.01) were significantly up-regulated in aged male mice vs. aged female mice, whereas miR-20b-5p (−2.10 fold; p < 0.05) was significantly down-regulated in aged male mice vs. aged female mice. Interestingly, miR-27a-3p, miR-27b-3p, miR-20a-5p, and miR-20b-5p expression significantly correlated with the thickness of the retinal PS layer (p < 0.01), retinal outer layers (p < 0.01) and Bruch’s membrane (p < 0.01). Our results showed that biological sex can influence the structure and function of the retina upon aging, suggesting that this difference may be underlined by the dysregulation of age-related mi-RNAs.